Analisis Pelaksanaan Pembelajaran Berdiferensiasi Pada Mata Pelajaran Sejarah (Studi pada SMA Negeri di Pontianak) - Edwin Mirzachaerulsyah (Peneliti.net, 2023)
Differentiated learning is an integral part of the independent curriculum. This study aims to (1) see the form of planning that has been carried out by history teachers in carrying out differentiated learning (2) what forms of evaluation have been carried out by history teachers. The research was conducted at two schools, namely public high school 1 and 10 Pontianak. The research method used is qualitative by collecting data through observation, interviews and documentation. the result of the research is that teachers plan differentiated learning by paying attention to its aspects and utilizing stakeholder networks and information during in-house training activities. The forms of evaluation that have been carried out include process evaluation such as observation and also evaluation in the form of tests